2014
DOI: 10.3892/ijo.2014.2251
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin-3-gallate inhibits cell growth, induces apoptosis and causes S phase arrest in hepatocellular carcinoma by suppressing the AKT pathway

Abstract: Abstract. Epigallocatechin-3-gallate (EGCG) has been shown to inhibit the growth and induce apoptosis of certain cancer cells. The aim of this study was to determine the role of EGCG in hepatocellular carcinoma (HCC) and the underlying mechanism(s) thereof. MTT assay was used to determine the cell growth inhibition by EGCG. Apoptosis induced by EGCG was investigated by both AO/EB staining and flow cytometry. The cell cycle distribution was analyzed by flow cytometry. The mRNA levels of the AKT pathway were ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 31 publications
0
31
1
Order By: Relevance
“…For instance, EGCG has attracted growing attention due to its low toxicity in normal cells and significant inhibitory effect on cancer cells (26,27). Our previous research demonstrated that EGCG significantly inhibits the growth of hepatocellular carcinoma cells SMMC7721 at 48 h (28). In this study, we assessed the apoptotic effects of EGCG in B lymphoma cells and investigated the possible molecular mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, EGCG has attracted growing attention due to its low toxicity in normal cells and significant inhibitory effect on cancer cells (26,27). Our previous research demonstrated that EGCG significantly inhibits the growth of hepatocellular carcinoma cells SMMC7721 at 48 h (28). In this study, we assessed the apoptotic effects of EGCG in B lymphoma cells and investigated the possible molecular mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Among the class of secondary metabolites, flavonoids stand out as efflux pump inhibitors particularly because they inhibit P-gp ATP-ase activity by interacting with the ATP-binding sites [62, 63]. The natural product polyphenol epigallocatechin-3-gallate (EGCG), the most abundant and active phenolic compound found in green tea, exhibits antitumor properties [64-66]. Numerous studies have demonstrated that EGCG affects many signaling pathways including Janus kinase (JAK)/signal transducer and activator of transcription (STAT), mitogen-activated protein kinases (MAPK), phosphoinositide 3-kinase (PI3K/AKT), WNT, Hedgehog (Hh) and NOTCH [67, 68].…”
Section: Phytometabolites Targeting Cscs Modulate Abc Transporters Kmentioning
confidence: 99%
“…Noh et al showed that EGCG improves Dermatophagoides pteronissinus extract-induced atopic dermatitis-like skin lesions in a mouse model by suppressing MIF [437]. In addition, EGCG can inhibit TNF-α [438], iNOS [439, 440], AKT [441], the CXC group of cytokines [442], and by by reducing the transcriptional activity of NF-κB, COX-2 expression and PGE-2 synthesis [443448]. Additionally, EGCG activates wild-type p53 [449451], and protects from p53 mutation [452].…”
Section: Low Toxicity Approachesmentioning
confidence: 99%